SPE Latin American and Caribbean Petroleum Engineering Conference 2001
DOI: 10.2118/69544-ms
|View full text |Cite
|
Sign up to set email alerts
|

ASP System Design for an Offshore Application in the La Salina Field, Lake Maracaibo

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe La Salina Field in the eastern coast of Lake Maracaibo, Venezuela, was designated as a Laboratorio Integrado de Campo (Integrated Field Laboratory, IFL) by PDVSA to evaluate the potential application of different EOR processes. One of the main goals at La Salina FIL was to evaluate the alkaline-surfactant-polymer (ASP) technology potential in an oil reservoir near the end of its waterflood life.La Salina produces a medium gravity crude oil (25 °API) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The additional production of oil using this method in the central well (number7) reached 13.4% of the OOIP. Furthermore, Hernandez and Larry J [10] indicated that economic efficiency of applying ASP flooding method is based on a series of experiments including: compatibility between the fluids, thermal stability of the chemicals, auto-formation of the emulsions, interfacial tension (oil and ASP solution), and trapping chemicals in the porous medium. Moreover, results of injection cores taken from Salina offshore field showed that when injecting 30% PV of ASP solution followed by 30 %PV of polymer pushing solution, 24.6% recovery of the OOIP was obtained.…”
Section: Reference Studiesmentioning
confidence: 99%
“…The additional production of oil using this method in the central well (number7) reached 13.4% of the OOIP. Furthermore, Hernandez and Larry J [10] indicated that economic efficiency of applying ASP flooding method is based on a series of experiments including: compatibility between the fluids, thermal stability of the chemicals, auto-formation of the emulsions, interfacial tension (oil and ASP solution), and trapping chemicals in the porous medium. Moreover, results of injection cores taken from Salina offshore field showed that when injecting 30% PV of ASP solution followed by 30 %PV of polymer pushing solution, 24.6% recovery of the OOIP was obtained.…”
Section: Reference Studiesmentioning
confidence: 99%